Superoxide generation by endothelial nitric oxide synthase: The influence of cofactors - Vásquez-Vivar, Jeannette (The National Academy of Sciences, 1998)
The mechanism of superoxide generation by endothelial nitric oxide synthase (eNOS) was investigated by the electron spin resonance spin-trapping technique using 5-diethoxyphosphoryl-5-methyl-1-pyrroline N-oxide. In the absence of calcium/calmodulin, eNOS produces low amounts of superoxide. Upon activating eNOS electron transfer reactions by calcium/calmodulin binding, superoxide formation is increased. Heme-iron ligands, cyanide, imidazole, and the phenyl(diazene)-derived radical inhibit superoxide generation. No inhibition is observed after addition of l-arginine, N(G)-hydroxy-l-arginine, l-thiocitrulline, and l-N(G)-monomethyl arginine to activated eNOS. These results demonstrate that superoxide is generated from the oxygenase domain by dissociation of the ferrous–dioxygen complex and that occupation of the l-arginine binding site does not inhibit this process. However, the concomitant addition of l-arginine and tetrahydrobiopterin (BH(4)) abolishes superoxide generation by eNOS. Under these conditions, l-citrulline production is close to maximal. Our data indicate that BH(4) fully couples l-arginine oxidation to NADPH consumption and prevents dissociation of the ferrous–dioxygen complex. Under these conditions, eNOS does not generate superoxide. The presence of flavins, at concentrations commonly employed in NOS assay systems, enhances superoxide generation from the reductase domain. Our data indicate that modulation of BH(4) concentration may regulate the ratio of superoxide to nitric oxide generated by eNOS.